Actualization of Sakai Sambayan Local Wisdom Values in Strengthening Citizen Engagement in Kedaloman Village, Tanggamus Regency - Pradanna, Satrio Alpen; Abdulkarim, Aim; Malihah, Elly; Hidayat, Obby Taufik (Universitas Muhammadiyah Ponorogo, 2023)
Citizen Engagement is one of the most important elements in social life. This engagement can bring up various positive contributions to a community. This activity is an important aspect of social responsibility as an active citizen. Youth participation in community activities involves community service (gotong-royong). Mutual cooperation will contribute to the growth and development of youth, as well as efforts to create community welfare. This research aims to determine the actualization of the Sakai Sambayan philosophy of youth people's life in the Kedaloman, Tanggamus district, Lampung, community in strengthening citizen engagement. The research method used in this study is a qualitative approach using studies cases. The observation technique employed participant observation by becoming a member of Ikatan Muli-Mekhanai Kebandakhan in Pekon Kedaloman (local youth association). Then, interviewing the head of the organization and village officials to find out about the actualization of Sakai Sambayan local wisdom values. This study indicates that understanding the concept of Sakai Sambayan itself influences the actualization of local wisdom values in young people. Through understanding these life principles, young people have a culture of shame if they do not participate in community activities. The actualization value of Sakai Sambayan among the youth of Kedaloman can be seen in their various efforts to actively participate in the community activities, such as community service, religious activities, and the preservation of the cultural heritage in Pekon Kedaloman.